Historia de la educación en el territorio achuar : estudio de caso en los centros educativos de Pakintsa y Kurintsa. - Shakaim Wajarai, Petsain Rufino (2018)
On the subject of the history of education in the Achuar territory: a case study in the Pakintsa and Kurintsa schools, the major effort has been to collect information, gathering the wisdom of the "junt" (olders) who have knowledge about the history of education in their schools. In both communities they had problems in educating their children, so there was no schooling. In the beginning, education consisted in the transmission of cultural elements and practices: in ancient times war between families, friends and neighbours was common. They were taught fishing, hunting, handicraft making, using the materials of their habitat with their relatives. The priorities of the communities and the concern for the war, the change was made by Father Luis Bolla, who came to socialize education in our Achuar territory, and is also grateful for the change of the old life and for planting educational centers in the Achuar nationality. Education has changed the way we live and has allowed the development of society by seeking the quality and warmth of our children's education. Many of the peoples have been left with peace in our Achuar territory, leaving war aside. Thanks to the positive ideas given by our brother Luis Bolla, which have encouraged us to constantly seek the liberation of practices that do not allow us to improve the lives of our families and communities.